Analisis Kebijakan Perubahan Capaian Pembelajaran(CP) Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti Elemen Sejarah Peradaban Islam Pada Kurikulum Merdeka - Zaimul Ihsan (Politik Islam, 2022)
Activity/Experience is the community's support for the candidacy of the candidate pairs Eka Putra and Richi Apriadi through the 2020 Tanah Datar district election, cannot be separated from political capital that comes from the role of the candidate pair's organizational activities before advancing in the nomination. Second, Local Political Elite Support is a number of candidate strengths from local political elites from political organizations, social organizations and even political parties who can represent their interests. by finding votes/voter support for candidate pairs. Eka-Richi has relations or insiders both from outside the party or only as sympathizers such as collaborating with all lines of society, both young people and community leaders who are able to make a product that cannot be imitated by other candidate pairs, namely free plows. , one event one village. Second, the problem encountered is the black campaign or black campaign that attacks every segment owned by Eka-Richi. Eka-Richi built such a neat solution in preventing bad things from black campaigns by various parties.